1974
DOI: 10.1002/j.2050-0416.1974.tb03603.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Polyphenols on the Rate of Haze Formation in Beer

Abstract: The effect of the addition of a range of monomeric, dimeric and polymeric polyphenols to beer on the rate of haze formation has been examined. Monomeric polyphenols had no significant effect on haze formation. The addition to beer of dimeric or polymeric polyphenols caused a large increase in the rate of haze formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

1975
1975
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…The proanthocyanidins and catechins were dissolved in beers pretreated with 500 ppm of PVPP at a concentration of 50 mg/liter. (6) o (4) o ( Portions of 10 ml of the mixtures were put in glass tubes (1.8 x 7 cm) closed with a septum cap, stored at 50 0 e for 4 and 7 days and then chilled at ooe for 40 min. The chill haze was measured nephelometrically with a ZeissPulfrich photometer.…”
Section: Changes In the Haze-forming Capacities Of Proanthocyanidins mentioning
confidence: 99%
“…The proanthocyanidins and catechins were dissolved in beers pretreated with 500 ppm of PVPP at a concentration of 50 mg/liter. (6) o (4) o ( Portions of 10 ml of the mixtures were put in glass tubes (1.8 x 7 cm) closed with a septum cap, stored at 50 0 e for 4 and 7 days and then chilled at ooe for 40 min. The chill haze was measured nephelometrically with a ZeissPulfrich photometer.…”
Section: Changes In the Haze-forming Capacities Of Proanthocyanidins mentioning
confidence: 99%
“…The extent of tannin-protein complex formation can be influenced by various factors such as: pH-Calderon et al 1968; Hagerman and Butler 1981;Oh et a1 1985;Hagerman and Klucher 1986;Oh and Hoff 1987;Yokotsuka and Singleton 1987;Spencer et Lea and Arnold 1978;Yokotsuka and Singleton 1987 proline richness of the protein-Oh et a1 1980; Hagerman andButler 1980,1981;Butler et a1 1984;Asquith et a1 1987;Bergmann and Mattice 1987;Spencer et a1 1988. In practical terms, tannin-protein interactions are important in the preparation and enjoyment of tea, wine, coffee, cider and beer. Proanthocyanidins in beers may be the origin of chill and permanant haze formation (Eastmond and Gardner 1974;McGuiness et a1 1975;Asano et a1 1984;Delcour et a1 1984), and residual wine proteins are generally considered to be detrimental to wine quality due to their role in the formation of hazes (Powers et a1 1988). Wine stability in this respect can be improved using proanthocyanidins immobilised on sepharose (Oh et a1 1985;Powers et a1 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Although the results presented here do not show a definitive link between polyphenol concentration and the haze level of the products, this is certainly an area worthy of further investigation with regards to flavoured lager beer products. Although this study did not attempt to discriminate between types of polyphenol, it has been shown previously that monomeric polyphenols have no significant effect on haze formation, whereas dimeric or polymeric polyphenols cause a large increase in the rate of haze formation . The specific type of polyphenol compound present is an important factor with regards to haze formation, with the proanthocyanidin class of polyphenols showing a particularly specific affinity for haze‐forming proteins .…”
Section: Resultsmentioning
confidence: 97%